Development of Web-Based Information System Using Linear Sequential Method at SMP Makna Bakti Jakarta Pusat - Endriansyah, Muhammad Try; Astuti, Rika; Ramadhan, Galuh Bakti (Universitas Trilogi, 2020)
The development of information and communication technology (ICT) which is growing rapidly nowadays, SMP MAKNA BAKTI JAKARTA PUSAT wants the application of information technology in a structured governance process in schools. One of the problems currently faced by SMP MAKNA BAKTI JAKARTA PUSAT is that the assessment process conducted by teachers is still done manually and is less effective. Constraints also occur when the subject teacher has finished assessing and must submit to the homeroom teacher. Constraints faced include delays in the collection of grades by subject teachers, and the length of time required for the homeroom teacher to recapitulate grades. And it is difficult for students to see the results of learning done by asking or waiting for confirmation from the subject teacher. The author intends to make a web-based information system application in the form of e- report cards. With the existence of a web-based information system, it is expected to be able to help in efficient management of entity data and a more structured assessment system for better implementation. In the design of the e-report system information on SMP MEAN BAKTI uses PHP programming language, with the use of MySQL database. The method used in this study is Sequential Linear